2019
DOI: 10.1021/acschemneuro.9b00244
|View full text |Cite
|
Sign up to set email alerts
|

A Cleaning Crew: The Pursuit of Autophagy in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second-most common neurodegenerative disorder, neuropathologically characterized by the aggregation of misfolded α-synuclein (α-syn) protein, which appears to be central to the onset and progression of PD pathology. Evidence from pioneering studies has highly advocated the existence of impaired autophagy pathways in the brains of PD patients. Autophagy is an evolutionarily conserved, homeostatic mechanism for minimizing abnormal protein aggregates and facilitating organelle turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…Indeed, genetic studies have revealed extensive links between autophagy and neurodegenerative diseases, and disruptions to autophagy may contribute to the development of these diseases. Since both reduced and excessive autophagy can be detrimental, the modulation of autophagy has been proposed as a new, effective way for treating some types of neurodegenerative diseases ( Mputhia et al, 2019 ; Parekh et al, 2019 ; Djajadikerta et al, 2020 ). Rapamycin, an allosteric mTOR inhibitor, is one of the most frequently studied autophagy inducers ( Bove et al, 2011 ); it acts by increasing lysosomal biogenesis by avoiding autophagosome accumulation and neuronal toxicity ( Dehay et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genetic studies have revealed extensive links between autophagy and neurodegenerative diseases, and disruptions to autophagy may contribute to the development of these diseases. Since both reduced and excessive autophagy can be detrimental, the modulation of autophagy has been proposed as a new, effective way for treating some types of neurodegenerative diseases ( Mputhia et al, 2019 ; Parekh et al, 2019 ; Djajadikerta et al, 2020 ). Rapamycin, an allosteric mTOR inhibitor, is one of the most frequently studied autophagy inducers ( Bove et al, 2011 ); it acts by increasing lysosomal biogenesis by avoiding autophagosome accumulation and neuronal toxicity ( Dehay et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, apelin-13 induced autophagy in rotenone treated cells, as indicated by the higher ratio of LC3B-II/LC3B-I, less p62, and α-synuclein accumulated in the cells. Autophagy dysfunction was supposed in α-synuclein aggregation, therefore, clearance of aggregated α-synuclein, via up-regulation of the autophagy-lysosomal pathway, could provide a pharmacologically viable approach to the treatment of PD [58,59]. Considering the presence of autophagy impairment in rotenone models, these results indicate that apelin-13 might serve as an autophagy inducer and exert protective effects against rotenone-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 88%
“…SYN interaction with mitochondria occurs at higher protein expression or impaired chaperone-SYN ratio; therefore, the pathological conditions result in the failing of its CMA-derived proteolytic degradations [24]. Therapeutic strategies aiming to increase the SYN degradation through activation of these clearance pathways have thus been deeply explored in order to re-establish physiological levels of the protein and prevent its accumulation in PD [25,42,43]. The most interactions of SYN with mitochondria occur in cells in the case of oxidative stress [44] that can promote SYN aggregation associated with mitochondrial dysfunction [45,46].…”
Section: Syn Mutations and Pathological Assembliesmentioning
confidence: 99%